The Emerging Role of GC-MSCs in the Gastric Cancer Microenvironment: From Tumor to Tumor Immunity - Zhaoji Pan; Yiqing Tian; Guoping Niu; Chengsong Cao (Hindawi Limited, 2019)
Mesenchymal stem cells (MSCs) have been declared to not only participate in wound repair but also affect tumor progression. Tumor-associated MSCs, directly existing in the tumor microenvironment, play a critical role in tumor initiation, progression, and development. And different tumor-derived MSCs have their own unique characteristics. In this review, we mainly describe and discuss recent advances in our understanding of the emerging role of gastric cancer-derived MSC-like cells (GC-MSCs) in regulating gastric cancer progression and development, as well as the bidirectional influence between GC-MSCs and immune cells of the tumor microenvironment. Moreover, we also discuss the potential biomarker and therapeutic role of GC-MSCs. It is anticipated that new and deep insights into the functionality of GC-MSCs and the underlying mechanisms will promote the novel and promising therapeutic strategies against gastric cancer.